Extraosseous Ewing sarcoma in children: a systematic review and meta-analysis of clinicodemographic characteristics - Ghandour, Maher; Lehner, Burkhard; Klotz, Matthias; Geisbüsch, Andreas; Bollmann, Jakob; Renkawitz, Tobias; Horsch, Axel (Children, 2022)
We conducted this systematic review to provide comprehensive evidence on the prevalence, clinical features and outcomes of young extraosseous Ewing sarcoma (EES) cases.
Gesehen am 21.02.2023